Preparation process of anti-breaking glass material

By spin-coating a mixture of modified nanosilicon dioxide, modified potassium titanate whiskers, quaternized silicon sol and hydrogen-containing silicone oil on the glass substrate, forming a drop-proof glass material, solving the shortcomings of existing glass materials in terms of impact resistance, stain resistance and wear resistance, and achieving higher glass performance needs.

CN119528449AActive Publication Date: 2025-02-28SHANDONG RENAULT LIGHT IND PRODUCTS CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411635990.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-28
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Existing glass materials have shortcomings in impact resistance, pollution resistance and wear resistance, and it is difficult to meet the high requirements of modern technology for glass performance.

Method used

By mixing and spin-coating the modified nanosilicon dioxide, modified potassium titanate whiskers, quaternized silicon sol and hydrogen-containing silicone oil onto the glass substrate, an anti-fall glass material is formed. The process includes a multi-step reaction and grafting process, improving the dispersion, compactness and cross-linking network of the material, enhancing its impact, stain and wear resistance.

Benefits of technology

It achieves excellent impact resistance, stain resistance and wear resistance of fall-proof glass materials, significantly improving its performance in practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137162270000031
    Figure BDA0005137162270000031
  • Figure BDA0005137162270000032
    Figure BDA0005137162270000032
  • Figure BDA0005137162270000033
    Figure BDA0005137162270000033
Patent Text Reader

Abstract

The invention discloses a preparation process of an anti-breaking glass material, and relates to the field of glass materials. When the anti-breaking glass material is prepared, nano silicon dioxide sequentially reacts with 3-(N-allylamino) propyltrimethoxysilane and ethylene oxide-2-methyl sodium sulfonate to obtain modified nano silicon dioxide; the preparation method comprises the following steps: uniformly mixing potassium titanate whiskers, maleic anhydride, methyl acrylate and 2-methyl-1, 3-butadiene to obtain modified potassium titanate whiskers; the preparation method comprises the following steps: reacting 5-(dimethylamino)-2-hydroxybenzaldehyde with 3-aminopropyl trimethoxy silane to obtain functionalized trimethoxy silane; then enabling tetraethoxysilane and the functionalized trimethoxysilane to react, and grafting 4-chlorobutene to obtain quaternized silica sol; uniformly mixing the modified nano silicon dioxide, the modified potassium titanate whisker, the quaternized silica sol and the hydrogen-containing silicone oil, and spin-coating a glass substrate with the mixture to obtain the anti-breaking glass material. The anti-breaking glass material prepared by the invention has excellent antifouling property, wear resistance and impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of glass materials, and specifically to a preparation process of a fall-proof glass material. Background Art

[0002] Amorphous materials have a wide range of applications in modern life and science and technology. The most typical one is glass. As an ancient and traditional material, glass is currently widely used in the communication industry, building materials, information display, optoelectronic industry, automotive industry, etc. From ordinary exterior wall glass to special heat-insulating glass; from delicate glass ornaments to precision glass substrates; from simple daily glass products to complex laboratory glass instruments. With the progress of technology, especially the advent of the intelligent era, higher requirements are put forward for the performance of glass, and it is necessary to continuously improve the mechanical, electrical, optical, and thermal properties of glass to meet the market requirements. Therefore, the present invention prepares a fall-proof glass material with excellent impact resistance. Summary of the Invention

[0003] The purpose of the present invention is to provide a preparation process of a fall-proof glass material to solve the problems existing in the prior art.

[0004] To solve the above technical problems, the present invention provides the following technical solutions:

[0005] A fall-proof glass material, which is prepared by uniformly mixing modified nano-silica, modified potassium titanate whiskers, quaternized silica sol, and hydrogen-containing silicone oil and spin-coating them on a glass substrate.

[0006] As an optimization, the glass substrate is obtained by uniformly mixing silica, alumina, sodium oxide, lithium oxide, potassium oxide, magnesium oxide, tin oxide, yttrium oxide, and lanthanum oxide and pouring them.

[0007] As an optimization, the quaternized silica sol is obtained by reacting 5-(dimethylamino)-2-hydroxybenzaldehyde with 3-aminopropyltrimethoxysilane, and then successively reacting with tetraethyl orthosilicate and 4-chlorobutene.

[0008] As an optimization, the modified potassium titanate whiskers are obtained by uniformly mixing potassium titanate whiskers, maleic anhydride, methyl acrylate, and 2-methyl-1,3-butadiene.

[0009] As an optimization, the potassium titanate whiskers are of industrial micron grade and are from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0010] As an optimization, the modified nano-silica is obtained by successively reacting nano-silica with 3-(N-allylamino)propyltrimethoxysilane and sodium 2-(2-methoxyethoxy)ethanesulfonate.

[0011] As an optimization, the nano-silica has a mesh size of 325 and is from Shandong Wanhua Tianhe New Materials Co., Ltd.

[0012] A preparation process of a fall-proof glass material includes the following preparation steps:

[0013] (1) Mix nano-silica, 3-(N-allylamino)propyltrimethoxysilane and absolute ethanol in a mass ratio of 1:(0.01 - 0.03):(15 - 25), stir at 60 - 70°C and 200 - 400 rpm for 3 - 5 h, naturally cool to room temperature and then filter, wash with absolute ethanol and deionized water 3 - 5 times respectively, and dry at 95 - 105°C for 4 - 6 h to obtain pre-modified nano-silica; Mix the pre-modified nano-silica, 2-(2-methoxyethoxy)ethyl methanesulfonate and methanol in a mass ratio of 1:(2 - 3):(45 - 55), reflux at 60 - 70°C for 5 - 7 h, perform rotary evaporation at 65 - 75°C for 1 - 2 h, wash with absolute ethanol 3 - 5 times, and dry at 70 - 80°C for 6 - 8 h to obtain modified nano-silica;

[0014] (2) Mix potassium titanate whiskers, maleic anhydride, methyl acrylate, 2-methyl-1,3-butadiene, azobisisobutyronitrile and isoamyl acetate in a mass ratio of 1:(1.8 - 2.0):(0.5 - 0.6):(0.6 - 0.7):(0.03 - 0.04):(13 - 15), stir in a nitrogen atmosphere at 70 - 80°C and 150 - 250 rpm for 7 - 9 h, naturally cool to room temperature and then centrifuge, wash with isoamyl acetate and petroleum ether 3 - 5 times respectively, dry at 40 - 50°C for 23 - 25 h, add a sodium hydroxide solution with a mass fraction of 50% - 60% which is 180 - 200 times the mass of the potassium titanate whiskers, perform ultrasonic dispersion at 20 - 30°C for 1 - 3 h and then filter, wash with deionized water 3 - 5 times, and dry at 55 - 65°C for 18 - 20 h to obtain modified potassium titanate whiskers;

[0015] (3) Mix 5-(dimethylamino)-2-hydroxybenzaldehyde, 3-aminopropyltrimethoxysilane alcohol solution, anhydrous magnesium sulfate and absolute ethanol in a mass ratio of 1:(19 - 20):(9 - 11):(72 - 73), stir in a nitrogen atmosphere at 40 - 50°C and 100 - 200 rpm for 5 - 7 h and then filter, perform rotary evaporation at 45 - 55°C for 1 - 2 h to obtain functionalized trimethoxysilane;

[0016] (4) Mix tetraethyl orthosilicate and isopropanol in a mass ratio of 1:(8-10), stir at 55-65°C and 100-200 rpm for 25-35 min, add hydrochloric acid to adjust the pH to 2-3, add deionized water 3-5 times the mass of tetraethyl orthosilicate at a uniform rate within 1-2 h, continue stirring for 4-6 h, add functionalized trimethoxysilane 1.4-1.6 times the mass of tetraethyl orthosilicate, and continue stirring for 4-6 h , naturally cooled to room temperature, aged for 1 to 3 days to obtain silica sol; silica sol, 4-chlorobutene, potassium iodide and propylene glycol monomethyl ether were mixed in a mass ratio of 1: (0.9 to 1.1): (0.01 to 0.03): (3 to 4), stirred in a nitrogen atmosphere at 75 to 85° C. and 100 to 200 rpm for 23 to 25 hours, and rotary evaporated at 115 to 125° C. for 25 to 35 minutes to obtain quaternary ammonium silica sol;

[0017] (5) The quaternary ammonium silica sol, modified potassium titanate whiskers, modified nano-silica and hydrogenated silicone oil are mixed in a mass ratio of 1: (0.037-0.038): (0.02-0.03): (0.18-0.19), stirred at 20-30°C and 300-400 rpm for 10-20 min, 0.01-0.02 times the mass of the quaternary ammonium silica sol of chloroplatinic acid is added and stirred for 5-15 min to obtain a film liquid; the film liquid is dropped onto a glass substrate, and a desktop coating machine is used to spin-coat the substrate at 2500-3500 r / min for 55-65 s to a thickness of 20-40 μm, and the substrate is heat treated at 190-210°C for 5-15 min, and allowed to stand at 70-90°C for 4-6 h to obtain a shatter-resistant glass material.

[0018] As an optimization, the reaction equation of the pre-modified nano-silica in step (1) is:

[0019]

[0020] As an optimization, the reaction equation for modifying the nano-silicon dioxide in step (1) is:

[0021]

[0022] As an optimization, the reaction equation for modifying the potassium titanate whiskers in step (2) is:

[0023]

[0024] As an optimization, the 3-aminopropyltrimethoxysilanol solution in step (3) is obtained by mixing 3-aminopropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:14.

[0025] As an optimization, the reaction equation of the functionalized trimethoxysilane in step (3) is:

[0026]

[0027] As an optimization, the reaction equation of the silica sol in step (4) is:

[0028]

[0029] As an optimization, the reaction equation of the quaternized silica sol in step (4) is:

[0030]

[0031] As an optimization, the preparation method of the glass substrate in step (5) is as follows: 60 parts of silicon dioxide, 13 parts of aluminum oxide, 3 parts of sodium oxide, 4 parts of lithium oxide, 2 parts of potassium oxide, 3 parts of magnesium oxide, 1 part of tin oxide, 0.6 parts of yttrium trioxide and 1.2 parts of lanthanum oxide are mixed by mass, melted in a pit furnace, kept warm at 1550-1650°C for 1.5-2.5 hours, stirred and exhausted, and then kept warm for another 1-2 hours, poured into a steel plate mold, kept warm at 500-600°C for 1-3 hours, cooled to room temperature with the furnace, and then polished.

[0032] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0033] When preparing the shatterproof glass material, the present invention sequentially reacts nano silicon dioxide with 3-(N-allylamino)propyltrimethoxysilane and sodium oxirane-2-ylmethanesulfonate to obtain modified nano silicon dioxide; potassium titanate whisker, maleic anhydride, methyl acrylate and 2-methyl-1,3-butadiene are mixed to obtain modified potassium titanate whisker; 5-(dimethylamino)-2-hydroxybenzaldehyde and 3-aminopropyltrimethoxysilane are reacted to obtain functionalized trimethoxysilane; ethyl orthosilicate and functionalized trimethoxysilane are reacted and then grafted with 4-chlorobutene to obtain quaternized silica sol; silicon dioxide, aluminum oxide, sodium oxide, lithium oxide, potassium oxide, magnesium oxide, tin oxide, yttrium trioxide and lanthanum oxide are mixed and cast to obtain a glass substrate; modified nano silicon dioxide, modified potassium titanate whisker, quaternized silica sol and hydrogen-containing silicone oil are mixed and spin-coated on the glass substrate to obtain the shatterproof glass material.

[0034] Firstly, nano-silica is reacted with 3-(N-allylamino)propyltrimethoxysilane and sodium 2-oxirane methanesulfonate in sequence to obtain modified nano-silica; potassium titanate whiskers, maleic anhydride, methyl acrylate and 2-methyl-1,3-butadiene are mixed to obtain modified potassium titanate whiskers; 3-(N-allylamino)propyltrimethoxysilane is grafted on the surface of nano-silica to improve the dispersibility of nano-silica, enhance the density of the film layer, and improve the wear resistance of the anti-drop glass material; epoxy is grafted on the nano-silica by reacting with epoxy groups and secondary amines; Sodium ethane-2-ylmethane sulfonate introduces negatively charged sulfonic acid groups to form hydrogen bonds with water molecules, increasing surface hydration and reducing the adhesion of oil and dust, while enhancing the electrostatic interaction with positively charged components, thereby improving the anti-fouling and impact resistance of the anti-drop glass material; by polymerizing on the surface of potassium titanate to form a deposition layer with carbon-carbon double bonds and a large number of carboxyl groups, the strong polarity of the carboxyl groups can form strong hydrogen bonds with polar substances, thereby improving hydrophilicity and reducing the adhesion of dirt, while enhancing the bonding force between the film liquid and the glass substrate, thereby further improving the anti-fouling and impact resistance of the anti-drop glass material.

[0035] Secondly, 5-(dimethylamino)-2-hydroxybenzaldehyde and 3-aminopropyltrimethoxysilane are reacted to obtain functionalized trimethoxysilane; then, ethyl orthosilicate and functionalized trimethoxysilane are reacted and then grafted with 4-chlorobutene to obtain quaternized silica sol; silicon dioxide, aluminum oxide, sodium oxide, lithium oxide, potassium oxide, magnesium oxide, tin oxide, yttrium trioxide and lanthanum oxide are mixed and cast to obtain a glass substrate; modified nano-silica, modified potassium titanate whiskers, quaternized silica sol and hydrogen-containing silicone oil are mixed and spin-coated on a glass substrate to obtain a shatter-resistant glass material; functionalized trimethoxysilane is synthesized by Schiff base reaction to form a hydrogen-bonded six-membered ring structure that can convert absorbed ultraviolet light into heat energy, thereby improving the anti-aging performance of the shatter-resistant glass material. ; Then, hydrochloric acid is used to catalyze hydrolysis and condensation to form a silica sol with a network structure, which promotes the bonding with the glass substrate and improves the impact resistance of the shatter-proof glass material; 4-chlorobutene is grafted through a quaternary ammonium reaction to form a positively charged quaternary ammonium structure, which enhances the electrostatic interaction between the sol and the inorganic components and improves the anti-fouling and impact resistance of the shatter-proof glass material; by doping Y2O3 and La2O3 as network modifiers, the network structure of the glass is reinforced, the degree of polymerization of the glass is enhanced, and the impact resistance of the shatter-proof glass material is improved; hydrogen-containing silicone oil is used to carry out a silylation reaction with modified nano-silica, modified potassium titanate whiskers, and quaternized silica sol to enrich the cross-linked network and further improve the impact resistance of the shatter-proof glass material. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0037] Embodiment 1:

[0038] A preparation process of a shatter-resistant glass material, the preparation process of the shatter-resistant glass material comprising the following preparation steps:

[0039] (1) Nano-silica, 3-(N-allylamino)propyltrimethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:0.01:15, stirred at 60°C and 200 rpm for 5 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 3 times respectively, and dried at 95°C for 6 hours to obtain pre-modified nano-silica; pre-modified nano-silica, sodium 2-oxirane methane sulfonate and methanol were mixed in a mass ratio of 1:2:45, refluxed at 60°C for 7 hours, rotary evaporated at 65°C for 2 hours, washed with anhydrous ethanol for 3 times, and dried at 70°C for 8 hours to obtain modified nano-silica;

[0040] (2) Potassium titanate whiskers, maleic anhydride, methyl acrylate, 2-methyl-1,3-butadiene, azobisisobutyronitrile and isoamyl acetate were mixed in a mass ratio of 1:1.8:0.5:0.6:0.03:13, stirred at 70°C and 150rpm for 9 hours in a nitrogen atmosphere, naturally cooled to room temperature and centrifuged, washed with isoamyl acetate and petroleum ether three times respectively, dried at 40°C for 25 hours, added with a 50% sodium hydroxide solution with a mass fraction of 180 times the mass of the potassium titanate whiskers, ultrasonically dispersed at 20°C for 3 hours, filtered, washed with deionized water three times, and dried at 55°C for 20 hours to obtain modified potassium titanate whiskers;

[0041] (3) 5-(dimethylamino)-2-hydroxybenzaldehyde, 3-aminopropyltrimethoxysilanol solution, anhydrous magnesium sulfate and anhydrous ethanol were mixed in a mass ratio of 1:19:9:72, stirred at 40°C and 100 rpm for 7 h in a nitrogen atmosphere, filtered, and rotary evaporated at 45°C for 2 h to obtain functionalized trimethoxysilane;

[0042] (4) Mix tetraethyl orthosilicate and isopropanol in a mass ratio of 1:8, stir at 55°C and 100 rpm for 35 min, add hydrochloric acid to adjust the pH to 2, add deionized water 3 times the mass of tetraethyl orthosilicate at a uniform rate within 1 h, continue stirring for 6 h, add functionalized trimethoxysilane 1.4 times the mass of tetraethyl orthosilicate, continue stirring for 6 h, cool naturally to room temperature, and age for 1 day to obtain silica sol; mix silica sol, 4-chlorobutene, potassium iodide and propylene glycol monomethyl ether in a mass ratio of 1:0.9:0.01:3, stir at 75°C and 100 rpm in a nitrogen atmosphere for 25 h, and rotary evaporate at 115°C for 35 min to obtain quaternary ammonium silica sol;

[0043] (5) The quaternary ammonium silica sol, modified potassium titanate whiskers, modified nano-silica and hydrogenated silicone oil were mixed in a mass ratio of 1:0.037:0.02:0.18, stirred at 20°C and 300 rpm for 20 min, 0.01 times the mass of the quaternary ammonium silica sol of chloroplatinic acid was added, and stirring was continued for 15 min to obtain a film liquid; the film liquid was dropped onto a glass substrate, and a desktop coating machine was used to spin coat at 2500 r / min for 55 s to a thickness of 20 μm, heat treated at 190°C for 15 min, and allowed to stand at 70°C for 6 h to obtain a shatter-resistant glass material.

[0044] Embodiment 2:

[0045] A preparation process of a shatter-resistant glass material, the preparation process of the shatter-resistant glass material comprising the following preparation steps:

[0046] (1) nano-silica, 3-(N-allylamino)propyltrimethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:0.02:20, stirred at 65°C and 300 rpm for 4 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 100°C for 5 hours to obtain pre-modified nano-silica; pre-modified nano-silica, sodium 2-oxirane methane sulfonate and methanol were mixed in a mass ratio of 1:2.5:50, refluxed at 65°C for 6 hours, rotary evaporated at 70°C for 1.5 hours, washed with anhydrous ethanol 4 times, and dried at 75°C for 7 hours to obtain modified nano-silica;

[0047] (2) Potassium titanate whiskers, maleic anhydride, methyl acrylate, 2-methyl-1,3-butadiene, azobisisobutyronitrile and isoamyl acetate were mixed in a mass ratio of 1:1.9:0.55:0.65:0.035:14, stirred at 75°C and 200 rpm for 8 h in a nitrogen atmosphere, cooled naturally to room temperature and centrifuged, washed with isoamyl acetate and petroleum ether for 4 times respectively, dried at 45°C for 24 h, added with a 55% sodium hydroxide solution with a mass fraction of 190 times the mass of the potassium titanate whiskers, ultrasonically dispersed at 25°C for 2 h, filtered, washed with deionized water for 4 times, and dried at 60°C for 19 h to obtain modified potassium titanate whiskers;

[0048] (3) 5-(dimethylamino)-2-hydroxybenzaldehyde, 3-aminopropyltrimethoxysilanol solution, anhydrous magnesium sulfate and anhydrous ethanol were mixed in a mass ratio of 1:19.5:10:72.5, stirred at 45°C and 150 rpm for 6 h in a nitrogen atmosphere, filtered, and rotary evaporated at 50°C for 1.5 h to obtain functionalized trimethoxysilane;

[0049] (4) Mix tetraethyl orthosilicate and isopropanol in a mass ratio of 1:9, stir at 60°C and 150rpm for 30min, add hydrochloric acid to adjust the pH to 2.5, add deionized water 4 times the mass of tetraethyl orthosilicate at a uniform rate within 1.5h, continue stirring for 5h, add functionalized trimethoxysilane 1.5 times the mass of tetraethyl orthosilicate, continue stirring for 5h, cool naturally to room temperature, and age for 2 days to obtain silica sol; mix silica sol, 4-chlorobutene, potassium iodide and propylene glycol monomethyl ether in a mass ratio of 1:1:0.02:3.5, stir at 80°C and 150rpm in a nitrogen atmosphere for 24h, and rotary evaporate at 120°C for 30min to obtain quaternary ammonium silica sol;

[0050] (5) The quaternary ammonium silica sol, modified potassium titanate whiskers, modified nano-silica and hydrogenated silicone oil were mixed in a mass ratio of 1:0.0375:0.025:0.185, stirred at 25°C and 350 rpm for 15 min, 0.015 times the mass of chloroplatinic acid of the quaternary ammonium silica sol was added, and stirring was continued for 10 min to obtain a film liquid; the film liquid was dropped onto a glass substrate, and spin-coated at 3000 r / min for 60 s to a thickness of 30 μm using a desktop coating machine, heat treated at 200°C for 10 min, and allowed to stand at 80°C for 5 h to obtain a shatter-resistant glass material.

[0051] Embodiment 3:

[0052] A preparation process of a shatter-resistant glass material, the preparation process of the shatter-resistant glass material comprising the following preparation steps:

[0053] (1) Nano-silica, 3-(N-allylamino)propyltrimethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:0.03:25, stirred at 70°C and 400 rpm for 3 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 5 times respectively, and dried at 105°C for 4 hours to obtain pre-modified nano-silica; pre-modified nano-silica, sodium 2-oxirane methane sulfonate and methanol were mixed in a mass ratio of 1:3:55, refluxed at 70°C for 5 hours, rotary evaporated at 75°C for 1 hour, washed with anhydrous ethanol for 5 times, and dried at 80°C for 6 hours to obtain modified nano-silica;

[0054] (2) Potassium titanate whiskers, maleic anhydride, methyl acrylate, 2-methyl-1,3-butadiene, azobisisobutyronitrile and isoamyl acetate were mixed in a mass ratio of 1:2.0:0.6:0.7:0.04:15, stirred at 80°C and 250rpm for 7h in a nitrogen atmosphere, naturally cooled to room temperature and centrifuged, washed with isoamyl acetate and petroleum ether for 5 times respectively, dried at 50°C for 23h, added with a sodium hydroxide solution with a mass fraction of 60% (200 times the mass of potassium titanate whiskers), ultrasonically dispersed at 30°C for 1h, filtered, washed with deionized water for 5 times, and dried at 65°C for 18h to obtain modified potassium titanate whiskers;

[0055] (3) 5-(dimethylamino)-2-hydroxybenzaldehyde, 3-aminopropyltrimethoxysilanol solution, anhydrous magnesium sulfate and anhydrous ethanol were mixed in a mass ratio of 1:20:11:73, stirred at 50°C and 200 rpm for 5 h in a nitrogen atmosphere, filtered, and rotary evaporated at 55°C for 1 h to obtain functionalized trimethoxysilane;

[0056] (4) Mix tetraethyl orthosilicate and isopropanol in a mass ratio of 1:10, stir at 65°C and 200 rpm for 25 min, add hydrochloric acid to adjust the pH to 3, add deionized water 5 times the mass of tetraethyl orthosilicate at a uniform rate within 2 h, continue stirring for 4 h, add functionalized trimethoxysilane 1.6 times the mass of tetraethyl orthosilicate, continue stirring for 4 h, cool naturally to room temperature, age for 4 days, and obtain silica sol; mix silica sol, 4-chlorobutene, potassium iodide and propylene glycol monomethyl ether in a mass ratio of 1:1.1:0.03:4, stir at 85°C and 200 rpm in a nitrogen atmosphere for 23 h, and rotary evaporate at 125°C for 25 min to obtain quaternary ammonium silica sol;

[0057] (5) The quaternary ammonium silica sol, modified potassium titanate whiskers, modified nano-silica and hydrogenated silicone oil were mixed in a mass ratio of 1:0.038:0.03:0.19, stirred at 30°C and 400 rpm for 10 min, 0.02 times the mass of the quaternary ammonium silica sol of chloroplatinic acid was added, and stirring was continued for 5 min to obtain a film liquid; the film liquid was dropped onto a glass substrate, and a desktop coating machine was used to spin coat at 3500 r / min for 55 s to a thickness of 40 μm, heat treated at 210°C for 5 min, and allowed to stand at 90°C for 4 h to obtain a shatter-resistant glass material.

[0058] Comparative Example 1:

[0059] A preparation process of a shatter-resistant glass material, the preparation process of the shatter-resistant glass material comprising the following preparation steps:

[0060] (1) nano-silica, 3-(N-allylamino)propyltrimethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:0.02:20, stirred at 65°C and 300 rpm for 4 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 100°C for 5 h to obtain pre-modified nano-silica;

[0061] (2) Potassium titanate whiskers, maleic anhydride, methyl acrylate, 2-methyl-1,3-butadiene, azobisisobutyronitrile and isoamyl acetate were mixed in a mass ratio of 1:1.9:0.55:0.65:0.035:14, stirred at 75°C and 200 rpm for 8 h in a nitrogen atmosphere, cooled naturally to room temperature and centrifuged, washed with isoamyl acetate and petroleum ether for 4 times respectively, dried at 45°C for 24 h, added with a 55% sodium hydroxide solution with a mass fraction of 190 times the mass of the potassium titanate whiskers, ultrasonically dispersed at 25°C for 2 h, filtered, washed with deionized water for 4 times, and dried at 60°C for 19 h to obtain modified potassium titanate whiskers;

[0062] (3) 5-(dimethylamino)-2-hydroxybenzaldehyde, 3-aminopropyltrimethoxysilanol solution, anhydrous magnesium sulfate and anhydrous ethanol were mixed in a mass ratio of 1:19.5:10:72.5, stirred at 45°C and 150 rpm for 6 h in a nitrogen atmosphere, filtered, and rotary evaporated at 50°C for 1.5 h to obtain functionalized trimethoxysilane;

[0063] (4) Mix tetraethyl orthosilicate and isopropanol in a mass ratio of 1:9, stir at 60°C and 150rpm for 30min, add hydrochloric acid to adjust the pH to 2.5, add deionized water 4 times the mass of tetraethyl orthosilicate at a uniform rate within 1.5h, continue stirring for 5h, add functionalized trimethoxysilane 1.5 times the mass of tetraethyl orthosilicate, continue stirring for 5h, cool naturally to room temperature, and age for 2 days to obtain silica sol; mix silica sol, 4-chlorobutene, potassium iodide and propylene glycol monomethyl ether in a mass ratio of 1:1:0.02:3.5, stir at 80°C and 150rpm in a nitrogen atmosphere for 24h, and rotary evaporate at 120°C for 30min to obtain quaternary ammonium silica sol;

[0064] (5) The quaternary ammonium silica sol, modified potassium titanate whiskers, pre-modified nano-silica and hydrogenated silicone oil were mixed in a mass ratio of 1:0.0375:0.025:0.185, stirred at 25°C and 350 rpm for 15 min, 0.015 times the mass of the quaternary ammonium silica sol of chloroplatinic acid was added and continued to stir for 10 min to obtain a film liquid; the film liquid was dropped onto a glass substrate, and a desktop coating machine was used to spin coat the substrate at 3000 r / min for 60 s to a thickness of 30 μm, heat treated at 200°C for 10 min, and allowed to stand at 80°C for 5 h to obtain a shatter-resistant glass material.

[0065] Comparative Example 2:

[0066] A preparation process of a shatter-resistant glass material, the preparation process of the shatter-resistant glass material comprising the following preparation steps:

[0067] (1) Potassium titanate whiskers, maleic anhydride, methyl acrylate, 2-methyl-1,3-butadiene, azobisisobutyronitrile and isoamyl acetate were mixed in a mass ratio of 1:1.9:0.55:0.65:0.035:14, stirred at 75°C and 200 rpm for 8 hours in a nitrogen atmosphere, cooled naturally to room temperature and centrifuged, washed with isoamyl acetate and petroleum ether for 4 times respectively, dried at 45°C for 24 hours, added with a sodium hydroxide solution with a mass fraction of 55% (190 times the mass of the potassium titanate whiskers), ultrasonically dispersed at 25°C for 2 hours, filtered, washed with deionized water for 4 times, and dried at 60°C for 19 hours to obtain modified potassium titanate whiskers;

[0068] (2) 5-(dimethylamino)-2-hydroxybenzaldehyde, 3-aminopropyltrimethoxysilanol solution, anhydrous magnesium sulfate and anhydrous ethanol were mixed in a mass ratio of 1:19.5:10:72.5, stirred at 45°C and 150 rpm for 6 hours in a nitrogen atmosphere, filtered, and rotary evaporated at 50°C for 1.5 hours to obtain functionalized trimethoxysilane;

[0069] (3) Ethyl orthosilicate and isopropanol were mixed in a mass ratio of 1:9, stirred at 60°C and 150 rpm for 30 min, hydrochloric acid was added to adjust the pH to 2.5, deionized water 4 times the mass of ethyl orthosilicate was added at a uniform rate within 1.5 h, stirring was continued for 5 h, functionalized trimethoxysilane 1.5 times the mass of ethyl orthosilicate was added, stirring was continued for 5 h, naturally cooled to room temperature, aged for 2 days, and silica sol was obtained; silica sol, 4-chlorobutene, potassium iodide and propylene glycol monomethyl ether were mixed in a mass ratio of 1:1:0.02:3.5, stirred at 80°C and 150 rpm in a nitrogen atmosphere for 24 h, and rotary evaporated at 120°C for 30 min to obtain quaternary ammonium silica sol;

[0070] (4) quaternized silica sol, modified potassium titanate whiskers and hydrogen-containing silicone oil were mixed in a mass ratio of

[0071] 1:0.0375:0.025:0.185, mix well, stir at 25 ° C and 350 rpm for 15 min, add chloroplatinic acid with a mass of 0.015 times that of quaternary ammonium silica sol and continue stirring for 10 min to obtain a film liquid; drop the film liquid on a glass substrate, use a desktop coater to spin coat at 3000 r / min for 60 s to a thickness of 30 μm, heat treat at 200 ° C for 10 min, and let stand at 80 ° C for 5 h to obtain a shatter-resistant glass material.

[0072] Comparative Example 3:

[0073] A preparation process of a shatter-resistant glass material, the preparation process of the shatter-resistant glass material comprising the following preparation steps:

[0074] (1) nano-silica, 3-(N-allylamino)propyltrimethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:0.02:20, stirred at 65°C and 300 rpm for 4 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 100°C for 5 hours to obtain pre-modified nano-silica; pre-modified nano-silica, sodium 2-oxirane methane sulfonate and methanol were mixed in a mass ratio of 1:2.5:50, refluxed at 65°C for 6 hours, rotary evaporated at 70°C for 1.5 hours, washed with anhydrous ethanol 4 times, and dried at 75°C for 7 hours to obtain modified nano-silica;

[0075] (2) 5-(dimethylamino)-2-hydroxybenzaldehyde, 3-aminopropyltrimethoxysilanol solution, anhydrous magnesium sulfate and anhydrous ethanol were mixed in a mass ratio of 1:19.5:10:72.5, stirred at 45°C and 150 rpm for 6 hours in a nitrogen atmosphere, filtered, and rotary evaporated at 50°C for 1.5 hours to obtain functionalized trimethoxysilane;

[0076] (3) Ethyl orthosilicate and isopropanol were mixed in a mass ratio of 1:9, stirred at 60°C and 150 rpm for 30 min, hydrochloric acid was added to adjust the pH to 2.5, deionized water 4 times the mass of ethyl orthosilicate was added at a uniform rate within 1.5 h, stirring was continued for 5 h, functionalized trimethoxysilane 1.5 times the mass of ethyl orthosilicate was added, stirring was continued for 5 h, naturally cooled to room temperature, aged for 2 days, and silica sol was obtained; silica sol, 4-chlorobutene, potassium iodide and propylene glycol monomethyl ether were mixed in a mass ratio of 1:1:0.02:3.5, stirred at 80°C and 150 rpm in a nitrogen atmosphere for 24 h, and rotary evaporated at 120°C for 30 min to obtain quaternary ammonium silica sol;

[0077] (4) The quaternary ammonium silica sol, potassium titanate whiskers, modified nano-silica and hydrogenated silicone oil were mixed in a mass ratio of 1:0.0375:0.025:0.185, stirred at 25°C and 350 rpm for 15 min, 0.015 times the mass of the quaternary ammonium silica sol of chloroplatinic acid was added and stirred for 10 min to obtain a film liquid; the film liquid was dropped onto a glass substrate, and a desktop coating machine was used to spin coat the substrate at 3000 r / min for 60 s to a thickness of 30 μm, heat treated at 200°C for 10 min, and allowed to stand at 80°C for 5 h to obtain a shatter-resistant glass material.

[0078] Comparative Example 4:

[0079] A preparation process of a shatter-resistant glass material, the preparation process of the shatter-resistant glass material comprising the following preparation steps:

[0080] (1) nano-silica, 3-(N-allylamino)propyltrimethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:0.02:20, stirred at 65°C and 300 rpm for 4 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 100°C for 5 hours to obtain pre-modified nano-silica; pre-modified nano-silica, sodium 2-oxirane methane sulfonate and methanol were mixed in a mass ratio of 1:2.5:50, refluxed at 65°C for 6 hours, rotary evaporated at 70°C for 1.5 hours, washed with anhydrous ethanol 4 times, and dried at 75°C for 7 hours to obtain modified nano-silica;

[0081] (2) Potassium titanate whiskers, maleic anhydride, methyl acrylate, 2-methyl-1,3-butadiene, azobisisobutyronitrile and isoamyl acetate were mixed in a mass ratio of 1:1.9:0.55:0.65:0.035:14, stirred at 75°C and 200 rpm for 8 h in a nitrogen atmosphere, cooled naturally to room temperature and centrifuged, washed with isoamyl acetate and petroleum ether for 4 times respectively, dried at 45°C for 24 h, added with a 55% sodium hydroxide solution with a mass fraction of 190 times the mass of the potassium titanate whiskers, ultrasonically dispersed at 25°C for 2 h, filtered, washed with deionized water for 4 times, and dried at 60°C for 19 h to obtain modified potassium titanate whiskers;

[0082] (3) 5-(dimethylamino)-2-hydroxybenzaldehyde, 3-aminopropyltrimethoxysilanol solution, anhydrous magnesium sulfate and anhydrous ethanol were mixed in a mass ratio of 1:19.5:10:72.5, stirred at 45°C and 150 rpm for 6 h in a nitrogen atmosphere, filtered, and rotary evaporated at 50°C for 1.5 h to obtain functionalized trimethoxysilane;

[0083] (4) TEOS and isopropanol were mixed in a mass ratio of 1:9, stirred at 60°C and 150 rpm for 30 min, hydrochloric acid was added to adjust the pH to 2.5, deionized water 4 times the mass of TEOS was added at a uniform rate within 1.5 h, stirring was continued for 5 h, functionalized trimethoxysilane 1.5 times the mass of TEOS was added, stirring was continued for 5 h, naturally cooled to room temperature, and aged for 2 days to obtain silica sol;

[0084] (5) Silica sol, modified potassium titanate whiskers, modified nano-silica and hydrogenated silicone oil were mixed in a mass ratio of 1:0.0375:0.025:0.185, stirred at 25°C and 350 rpm for 15 min, 0.015 times the mass of quaternary ammonium silicate chloroplatinic acid was added and stirred for 10 min to obtain a film liquid; the film liquid was dropped onto a glass substrate, and spin-coated at 3000 r / min for 60 s to a thickness of 30 μm using a desktop coating machine, heat treated at 200°C for 10 min, and allowed to stand at 80°C for 5 h to obtain a shatter-resistant glass material.

[0085] Test Case

[0086] 1. Antifouling

[0087] Test method: Take samples of the same size as the shatterproof glass material obtained in each embodiment and the comparative example, apply a dust layer on the sample, record the situation of the dust layer being washed by water by dripping water, and calculate the anti-fouling rate = clean area / experimental area*100%.

[0088] 2. Wear resistance

[0089] Test method: Take the shatterproof glass material obtained in each embodiment and the control example of the same size and weigh m0, use a wear test system, rub back and forth 100 times with a piece of steel wool weighing 200g under a pressure of 10kPa, weigh m1 again, and calculate the wear rate = (m0-m1) / m0*100%.

[0090] 3. Impact resistance

[0091] Test method: Take samples of the same size of 30cm×20cm for the shatterproof glass materials obtained in each embodiment and the comparative example, place a steel spherical impactor with a radius of 25mm and a mass of 510g 2m above the sample, and impact the center of the sample in a free fall manner. Use a high-speed camera to capture the number of radial cracks near the impact point during the impact process.

[0092] Table 1 below shows the analysis results of the anti-fouling, wear resistance and impact resistance of the shatterproof glass materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0093] Table 1

[0094] Anti-fouling rate % Wear rate % Number of radial cracks / piece Example 1 98.6 1.3 8 Example 2 99.5 0.9 7 Example 3 98.4 1.6 8 Comparative example 1 82.8 2.3 16 Comparative example 2 79.6 29.7 23 Comparative example 3 81.3 3.1 21 Comparative example 4 45.9 2.4 39

[0095] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the shatterproof glass material prepared by the present invention has good anti-fouling, wear resistance and impact resistance.

[0096] By comparison, Examples 1, 2, and 3 have higher anti-fouling rates and fewer radial cracks than Example 1, indicating that sodium 2-ethylene oxide sulfonate is grafted onto nano-silica by the reaction of epoxy groups and secondary amines, and negatively charged sulfonic acid groups are introduced to hydrogen bond with water molecules, thereby increasing surface hydration and reducing the adhesion of oil and dust. At the same time, the electrostatic interaction with positively charged components is enhanced, thereby improving the anti-fouling and impact resistance of the shatter-resistant glass material.

[0097] By comparison, compared with Example 2, Examples 1, 2, and 3 have higher anti-fouling rates, and lower wear rates and radial crack counts, which indicates that grafting 3-(N-allylamino)propyltrimethoxysilane on the surface of nano-silica can improve the dispersibility of nano-silica, enhance the density of the film layer, and improve the wear resistance of the shatter-resistant glass material; and utilizing hydrogen-containing silicone oil and modified nano-silica to undergo a silylation reaction to enrich the cross-linking network and improve the impact resistance of the shatter-resistant glass material.

[0098] By comparison, compared with Example 3, Examples 1, 2, and 3 have a higher anti-fouling rate and fewer radial cracks, which indicates that a deposition layer with carbon-carbon double bonds and a large number of carboxyl groups is formed on the surface of potassium titanate through polymerization. The strong polarity of the carboxyl groups can form strong hydrogen bonds with polar substances, thereby improving hydrophilicity and reducing the adhesion of dirt, while enhancing the bonding force between the film liquid and the glass substrate, further improving the anti-fouling and impact resistance of the anti-drop glass material; hydrogen-containing silicone oil is used to carry out a silylation reaction with modified potassium titanate whiskers to enrich the cross-linking network and further improve the impact resistance of the anti-drop glass material.

[0099] By comparison, compared with Example 4, Examples 1, 2, and 3 have higher anti-fouling rates and fewer radial cracks, which indicates that 4-chlorobutene is grafted via quaternary ammonium reaction to form a positively charged quaternary ammonium structure, thereby enhancing the electrostatic interaction between the sol and the inorganic components and improving the anti-fouling and impact resistance of the shatter-resistant glass material. By using hydrogenated silicone oil and quaternized silica sol to undergo a silylation reaction, the cross-linking network is enriched to further improve the impact resistance of the shatter-resistant glass material.

[0100] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A process for preparing a drop-resistant glass material, characterized in that: The anti-drop glass material is prepared by mixing modified nano-silicon dioxide, modified potassium titanate whiskers, quaternary ammonium silica sol and hydrogen-containing silicone oil and spin coating the mixture on a glass substrate; The glass substrate is obtained by mixing and casting silicon dioxide, aluminum oxide, sodium oxide, lithium oxide, potassium oxide, magnesium oxide, tin oxide, yttrium oxide and lanthanum oxide; The quaternized silica sol is obtained by reacting 5-(dimethylamino)-2-hydroxybenzaldehyde with 3-aminopropyltrimethoxysilane, and then reacting with ethyl orthosilicate and 4-chlorobutene in sequence; The modified potassium titanate whisker is obtained by mixing potassium titanate whisker, maleic anhydride, methyl acrylate and 2-methyl-1,3-butadiene; The modified nano silicon dioxide is obtained by sequentially reacting nano silicon dioxide with 3-(N-allylamino)propyltrimethoxysilane and sodium oxirane-2-ylmethanesulfonate.

2. The process for preparing a shatter-resistant glass material according to claim 1, characterized in that: The method comprises the following preparation steps: (1) mixing nano-silica, 3-(N-allylamino)propyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:(0.01-0.03):(15-25), stirring at 60-70°C and 200-400 rpm for 3-5 hours, naturally cooling to room temperature and filtering, washing with anhydrous ethanol and deionized water for 3-5 times respectively, and drying at 95-105°C for 4-6 hours to obtain pre-modified nano-silica; mixing pre-modified nano-silica, sodium 2-oxirane methane sulfonate and methanol in a mass ratio of 1:(2-3):(45-55), reflux at 60-70°C for 5-7 hours, rotary evaporation at 65-75°C for 1-2 hours, washing with anhydrous ethanol for 3-5 times, and drying at 70-80°C for 6-8 hours to obtain modified nano-silica; (2) potassium titanate whiskers, maleic anhydride, methyl acrylate, 2-methyl-1,3-butadiene, azobisisobutyronitrile and isoamyl acetate are mixed in a mass ratio of 1:(1.8-2.0):(0.5-0.6):(0.6-0.7):(0.03-0.04):(13-15), stirred in a nitrogen atmosphere at 70-80°C and 150-250 rpm for 7-9 hours, cooled naturally to room temperature and centrifuged, washed with isoamyl acetate and petroleum ether for 3-5 times respectively, dried at 40-50°C for 23-25 ​​hours, added with a sodium hydroxide solution with a mass fraction of 50%-60% (180-200 times the mass of the potassium titanate whiskers), ultrasonically dispersed at 20-30°C for 1-3 hours, filtered, washed with deionized water for 3-5 times, and dried at 55-65°C for 18-20 hours to obtain modified potassium titanate whiskers; (3) 5-(dimethylamino)-2-hydroxybenzaldehyde, 3-aminopropyltrimethoxysilanol solution, anhydrous magnesium sulfate and anhydrous ethanol are mixed in a mass ratio of 1:(19-20):(9-11):(72-73), stirred in a nitrogen atmosphere at 40-50° C. and 100-200 rpm for 5-7 hours, filtered, and rotary evaporated at 45-55° C. for 1-2 hours to obtain functionalized trimethoxysilane; (4) Mix tetraethyl orthosilicate and isopropanol in a mass ratio of 1:(8-10), stir at 55-65°C and 100-200 rpm for 25-35 min, add hydrochloric acid to adjust the pH to 2-3, add deionized water 3-5 times the mass of tetraethyl orthosilicate at a uniform rate within 1-2 h, continue stirring for 4-6 h, add functionalized trimethoxysilane 1.4-1.6 times the mass of tetraethyl orthosilicate, and continue stirring for 4-6 h , naturally cooled to room temperature, aged for 1 to 3 days to obtain silica sol; silica sol, 4-chlorobutene, potassium iodide and propylene glycol monomethyl ether were mixed in a mass ratio of 1: (0.9 to 1.1): (0.01 to 0.03): (3 to 4), stirred in a nitrogen atmosphere at 75 to 85° C. and 100 to 200 rpm for 23 to 25 hours, and rotary evaporated at 115 to 125° C. for 25 to 35 minutes to obtain quaternary ammonium silica sol; (5) The quaternary ammonium silica sol, modified potassium titanate whiskers, modified nano-silica and hydrogenated silicone oil are mixed in a mass ratio of 1: (0.037-0.038): (0.02-0.03): (0.18-0.19), stirred at 20-30°C and 300-400 rpm for 10-20 min, 0.01-0.02 times the mass of the quaternary ammonium silica sol of chloroplatinic acid is added and stirred for 5-15 min to obtain a film liquid; the film liquid is dropped onto a glass substrate, and a desktop coating machine is used to spin-coat the substrate at 2500-3500 r / min for 55-65 s to a thickness of 20-40 μm, and the substrate is heat treated at 190-210°C for 5-15 min, and allowed to stand at 70-90°C for 4-6 h to obtain a shatter-resistant glass material.

3. The process for preparing a shatter-resistant glass material according to claim 2, characterized in that: The reaction equation of the pre-modified nano-silica in step (1) is:

4. The process for preparing a shatter-resistant glass material according to claim 2, characterized in that: The reaction equation for the modified nano-silicon dioxide in step (1) is:

5. The process for preparing a shatterproof glass material according to claim 2, characterized in that: The reaction equation for modifying the potassium titanate whiskers in step (2) is:

6. The process for preparing a shatter-resistant glass material according to claim 2, characterized in that: The 3-aminopropyltrimethoxysilanol solution in step (3) is obtained by mixing 3-aminopropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:

14.

7. The process for preparing a shatter-resistant glass material according to claim 2, characterized in that: The reaction equation of the functionalized trimethoxysilane in step (3) is:

8. The process for preparing a shatter-resistant glass material according to claim 2, characterized in that: The reaction equation of the silica sol in step (4) is:

9. The process for preparing a shatter-resistant glass material according to claim 2, characterized in that: The reaction equation of the quaternized silica sol in step (4) is:

10. The process for preparing a shatter-resistant glass material according to claim 2, characterized in that: The preparation method of the glass substrate in step (5) is as follows: 60 parts of silicon dioxide, 13 parts of aluminum oxide, 3 parts of sodium oxide, 4 parts of lithium oxide, 2 parts of potassium oxide, 3 parts of magnesium oxide, 1 part of tin oxide, 0.6 parts of yttrium trioxide and 1.2 parts of lanthanum oxide are mixed by mass, melted in a pit furnace, kept warm at 1550-1650°C for 1.5-2.5 hours, stirred and exhausted, and then kept warm for 1-2 hours, poured into a steel plate mold, kept warm at 500-600°C for 1-3 hours, cooled to room temperature with the furnace, and then polished.

Citation Information

Patent Citations

  • Modified silica sol, and preparation method and application thereof

    CN105176179A

  • Organosilicone super-hydrophobic coating material, preparation method therefor and application of organosilicone super-hydrophobic coating material

    CN106479359A

  • Anti-yellowing leather finishing emulsion

    CN111004556A

  • Organic-inorganic hybrid anti-fog coating and preparation method thereof

    CN111574899A

  • Normal-temperature curing inorganic paint and preparation method thereof

    CN112625470A